The Lord of Rings, The Return of the king - Tolkien, J. R. R. (HarperCollins, London, 2012)
The armies of the Dark Lord Sauron are massing as his evil shadow spreads ever wider. Men, Dwarves, Elves and Ents unite forces to do battle agains the Dark. Meanwhile, Frodo and Sam struggle further into Mordor in their heroic quest to destroy the One Ring